Effects of vitamin and mineral supplementation on total and cancer mortality (Linxian General Population Randomised Nutrition Intervention Trial): results from the 25-year post-trial follow-up. (December 2017) - Wang, Shao-Ming; Taylor, Philip R; Fan, Jin-Hu; Pfeiffer, Ruth; Gail, Mitchell H; Liang, He; Murphy, Gwen A; Dawsey, Sanford M; Qiao, You-Lin; Abnet, Christian C
Abstract: Background: A beneficial effect of daily supplementation with a combination of selenium, vitamin E, and beta-carotene was observed on total and cancer mortality in a Chinese population, and this protective effect endured for 10 years post-intervention. We aimed to study the longer durability of this effect. Methods: This randomised, double-blind, placebo-controlled trial was conducted in four communes in Linxian, China, from 1986 to 1991. Active follow-up continued until 2016. 29 584 residents aged 40–69 years randomly received supplementations based on a factorial design. They received either factor A (retinol/zinc), B (riboflavin/niacin), C (vitamin C/molybdenum), or D (selenium/vitamin E/beta-carotene), or placebo daily for 5·25 years. The primary endpoints were total and cancer mortality. We used hazard ratios (HRs) and 95% CIs to identify the intervention effects of four different factors using Cox proportional hazards models. Ethics approval was obtained from the Institutional Review Board of the Cancer Hospital, Chinese Academy of Medical Sciences and the US National Cancer Institute. This trial is registered withClinicalTrials.gov, numberNCT00342654 . Findings: Up to 2016, the interventions showed no effect on total mortality, overall, or by sex. The previously reported protective effect of factor D against total mortality was lost after 10 years from the end of the intervention. The protective effect of factor D for gastric cancer was attenuated (HR 0·93, 95% CI 0·85–1·01; p=0·10), but a newly apparent protective effect against oesophageal cancer was found for factor B (0·92, 0·85–1·00; p=0·04). Other associations, both protective and adverse, were observed for specific causes of death. Protective effects were found in people younger than 55 years at baseline against death from non-upper gastrointestinal cancer for factor A (0·80, 0·69–0·92; p=0·002), and against death from stroke for factor C (0·89, 0·82–0·96; p=0·002). By contrast, we found an increased risk of esophageal cancer for patients who began the intervention after age 55 years for factor C (1·16, 1·04–1·30; p=0·01) and factor D (1·20, 1·07–1·34; p=0·002). Interpretation: Short-term supplementation with vitamins and minerals is unlikely to have a meaningful effect on mortality more than a decade after the supplementation ends, even in a nutritionally deprived population. Funding: National Cancer Institute contracts (N01-SC-91030, N01-RC-47701 and HHSN261201200034C to the Cancer Hospital/Institute, Chinese Academy of Medical Sciences).